Gender : roles & rights - Issitt, Micah L. (Opinions throughout history., 2018)
This book provides an essential resource for history and social studies research and an accessible commentary on the ways in which the idea of gender roles have evolved. It discusses the complex issues of gender roles and gender rights throughout history, and includes a timeline of significant events related to gender roles and rights, from 1533 to 2018.